2017
DOI: 10.1080/15376516.2017.1354413
|View full text |Cite
|
Sign up to set email alerts
|

T-2 toxin induces apoptosis via the Bax-dependent caspase-3 activation in mouse primary Leydig cells

Abstract: To explore the toxic effect of T-2 toxin on mouse Leydig cells and its underlying molecular mechanisms, we isolated Leydig cells from mature mice, set-up Leydig cells culture, treated cells with T-2 toxin, evaluated cell proliferation, detected the caspase-3 activity, mitochondrial activity and apoptosis rate, and measured the mRNA levels of Bcl-2, Bax, PARP and caspase-3. T-2 toxin inhibited cell proliferation at concentrations higher than 10 M or time more than 12 h, T-2 toxin also decreased Bcl-2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…A wealth of research papers clearly indicate a negative influence of T-2 toxin on the hematocytes, hepatocytes, chondrocytes, intestinal function, immune system, and reproductive system (Adhikari et al, 2017; He et al, 2012; Huang et al, 2018; Leal et al, 1998; Moosavi et al, 2016; Wu et al, 2017; Yang et al, 2010; Zhang et al, 2018). Our research team has also reported the negative effects of T-2 toxin on male fertility and other reproductive pathologies in male animals (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wealth of research papers clearly indicate a negative influence of T-2 toxin on the hematocytes, hepatocytes, chondrocytes, intestinal function, immune system, and reproductive system (Adhikari et al, 2017; He et al, 2012; Huang et al, 2018; Leal et al, 1998; Moosavi et al, 2016; Wu et al, 2017; Yang et al, 2010; Zhang et al, 2018). Our research team has also reported the negative effects of T-2 toxin on male fertility and other reproductive pathologies in male animals (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and purification of Leydig cells were performed according to our previous methods (Zhang et al, 2018). In brief, Leydig cells were isolated from testes of 60- to 90-day Kunming mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative stress induced by T-2 promotes Fas upregulation, p53 activation, down-regulation of Bcl-2 and up-regulation of the pro-apoptotic factor Bax causing cytochrome C release, caspase 3 activation and cell apoptosis (Chen et al, 2008;Zhang et al, 2018) ( Figure 2). ROS generation causes a decrease in Nrf2 expression, changes in the intracellular antioxidant enzymes GPx, GR, SOD and CAT, promoting a decrease in GSH level and an increase in MDA level (Wu et al, 2014b;Yang et al, 2016).…”
Section: T-2 Toxinmentioning
confidence: 99%
“…T‐2 toxin, a trichothecene mycotoxin produced by several species of Fusarium , has hepatotoxic, hematotoxic, immunotoxic, and genotoxic properties . Previous studies have provided evidence that T‐2 toxin can induce testicular oxidative damage and cause apoptosis in mouse Leydig cells …”
Section: Introductionmentioning
confidence: 99%